Thermodynamics and interfacial properties for self-assembly behaviour of methyl-imidazolium monomeric surfactants - Jaswinder Kaur; Roheela Farzeen; Swinky Pathania; Tarlok Singh Banipal; Manpreet Singh; Madan Lal; Nandita Thakur; Sanjay Kumar Upadhyaya; Kamal Kishore (Chemical Thermodynamics and Thermal Analysis)
A chain of three imidazolium monomeric surfactants have been synthesized and further analysed by 13C NMR, 1H NMR, FTIR and TGA for number & types of protons, types of carbon atoms, purity and the thermal stability. The conductance measurements of all the three synthesized monomeric surfactants have been checked at 288 K, 293 K, 298 K and 303 K using water as solvent. The conductivity results have indicated that these monomeric surfactants behave like weak electrolytes. Critical study of thermodynamic properties like ∆GoM, ∆HoM, ∆SoM have confirmed that out of aggregation and dissociation, the micellization is more preferred over the dissociation process after critical micellar concentration. Density and viscosity measurements were indicating the presence of significant interactions between monomeric surfactants and molecules of water in dilute solutions. Surface-active properties have shown that imidazolium monomeric surfactants are worthy candidates to lesser the interfacial tension and having the affinity to form micelles in the bulk solution after CMC. Critical analysis of surface tension has confirmed that higher the hydrophobic chain- length, greater was the capacity to reduce the surface tension at interface.